2006
DOI: 10.1116/1.2197513
|View full text |Cite
|
Sign up to set email alerts
|

dc thermal plasma synthesis and properties of zinc oxide nanorods

Abstract: In this research, a dc thermal plasma reactor was used to produce ZnO nanorods with a diameter of about 30nm and a length of 100–200nm. In the photocatalytic study, visible light absorption of the ZnO nanorods was achieved by doping up to a few thousands ppm of nitrogen. The nitrogen-doped ZnO nanorods under the visible light radiation exhibited excellent antimicrobial ability. UV-visible spectroscopy of the N-doped ZnO nanorods annealed in a reductive atmosphere revealed a strong absorption of near-IR light s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Among them, introduction of transition metal doping states will lead to an improved visible light photocatalytic activity due to the band-gap narrowing, resulting from the creation of dopant energy levels below the conduction band [13,15,16]. On the other hand, it has been demonstrated that hybridizing two different semiconductors can greatly decrease the photogenerated charge carriers' (electron-hole pairs) recombination probability and increase the lifetime of charge carriers, thus promoting photocatalytic efficiency [17,18]. One of the effective methodologies is to insert other semiconductor guest particles into the interlayer spacing of the 2-D semiconductor host lattices to fabricate a heterojunction structure.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, introduction of transition metal doping states will lead to an improved visible light photocatalytic activity due to the band-gap narrowing, resulting from the creation of dopant energy levels below the conduction band [13,15,16]. On the other hand, it has been demonstrated that hybridizing two different semiconductors can greatly decrease the photogenerated charge carriers' (electron-hole pairs) recombination probability and increase the lifetime of charge carriers, thus promoting photocatalytic efficiency [17,18]. One of the effective methodologies is to insert other semiconductor guest particles into the interlayer spacing of the 2-D semiconductor host lattices to fabricate a heterojunction structure.…”
Section: Introductionmentioning
confidence: 99%
“…N 2 gas was employed to form the plasma in a novel DC plasma reactor (detail of the plasma reactor has been reported elsewhere [8,9]). The zinc powders were fed into plasma flame at the rate of 1.0 kg/ h through a carrier gas (i.e.…”
Section: Synthesis Of Zno Nanoparticlesmentioning
confidence: 99%
“…However, the bandgap energies are large (about 3.2 eV), which means that both semiconductors can only be excited for photocatalytic uses under UV light illumination with the wavelength equal to or less than 385 nm. It is noted that visible light with spectral wavelength between 400 and 700 nm accounts for about 45% of the total energy of the solar radiation, while UV light occupies less than 10% [9]. Therefore, it is of great interest to improve the photocatalytic activity for practical photocatalytic applications under visible light.…”
Section: Introductionmentioning
confidence: 99%